Internalisasi Nilai-Nilai Islam Terhadap Siswa Sekolah Dasar Melalui Pembelajaran Matematika Terintegrasi Al-Qur'an - Supiarmo, M. Gunawan; Mardhiyatirrahmah, Liny; Rizqiyah, Anisatur (Program Pascasarjana IAIN Langsa, 2024)
Internalizing Islamic values in school learning. During this time, the responsibility has been placed more on the teacher of Islamic Religious Education, while teachers of other subjects are more focused on the general learning material. This led to the internalization of Islamic values through one path considered less successful in shaping student religious behavior. Indicators of this failure are the rise in criminal acts, asylum, drug use, and other violations among students and adolescents. So, there needs to be a change in the school curriculum that places the cultivation of Islamic values at the centre of attention from an early age, by integrating religious values into all subjects, including mathematics. This research aims to find an effective method of dealing with the moral problems faced by elementary school students. Several previous studies have explored mathematical concepts in the Qur'an, and the results show that Islamic values in the learning of mathematics can be internalized by paying attention to the relevant verses of the Quran. The research is carried out through descriptive methods with the study of literature, using various sources such as theses, research reports, articles, and books. The results show that the Islamic values in mathematical learning integration al-Qur'an can be internalized to students by applying the strategy of infusion, analogy, narration, and uswah hasanah.